Respon Fisiologis Domba Ekor Tipis Terhadap Waktu Pemberian Pakan Yang Berbeda - Gayuh Syaikhullah; M. Adhyatma; Himmatul Khasanah (Jurnal Sains dan Teknologi Peternakan, 2020)
This study aimed to examine the relationship of feeding time on physiological response and the effect on the behavior of Javanese thin-tailed sheep. The total population of the study was 12 sheep. The treatment in this study is feeding time in the morning (W1) and evening (W2). Parameters that had been observed were heart rate, respiration rate, rectal temperature. This research design used was a completely randomized design. Feeding at different times did not affect daily body weight gain. However, feeding at different times affects the physiological response of thin tail sheep. W1 has a higher heart rate value at daytime of 80.65 ± 3.49 but has a lower value in the afternoon at 75.26 ± 4.20. Respiration rates W1 in the morning and evening were 32.06 ± 2.69 and 51.88 ± 3.43. Rectal temperature W1 lower in the morning at 37.76 ± 0.05. Physiological response of thin tail sheep which were fed with different feeding times indicated that the heart rate, respiration rate, and rectal temperature were still in normal condition.